A high-performance bionic pressure memory device based on piezo-OLED and piezo-memristor as luminescence-fish neuromorphic tactile system. (November 2020) - Jiang, Chengming; Li, Qikun; Sun, Nan; Huang, Jijie; Ji, Ruonan; Bi, Sheng; Guo, Qinglei; Song, Jinhui
Abstract: For the mimicry of biological neuromorphic tactile system, an intriguing challenge is how to produce a multi-functioning electronic devices of sensing force like skins and memorizing information like brains. However, current pressure sensors can only detect real-time force information, which vanishes after removing external stimulations, and present serious barriers in terms of the integrating demand of pressure sensors and memory elements as bionic pressure memory. Inspired by the luminescence-fish neuromorphic tactile system, a high-performance dual-excited pressure memory (DPM) device with the piezo-OLED array and piezo-memristor array is demonstrated in the present study. The DPM device can actively sense the tactile information and memorize the mapping images by transferring pressure signals to resistance signals as the bionic electronic-skin. Furthermore, this device with the double piezo structure for both photo- and potential-excitations can retain the memorized information with a high on/off ratio of ~810 and a stable storage of <4% resistance attenuation. The corresponding tactile memory functions are also exhibited as artificial intelligence interactions with the tasks of pressure mapping recognition. The proof-of-concept device can pave the way for bionic neuromorphic tactile systems as the future high-performance wearable electronics, intelligent electronics, and handicapped auxiliary assistance. Graphical abstract: Image 1 Highlights: The flexible DPM device is realized by the double piezo-enhanced structures from the inspiration of luminescence-fish. The device exhibits a high on/off ratio of ~810 by dual-excitation processes. The high stable storage of the DPM can be obtained with little resistance variation (<4%) for the duration of 2 months. The pixel signals of the device can be erased and rewritten as the functions of the neuromorphic tactile system. The integrated DPM device demonstrates excellent mapping capacities of force-sensing and information-storing.